DRIVERS OF LONG-TERM CONVERGENCE. FOCUS ON ROMANIA - MANUELA UNGURU; RAZVAN VOINESCU (Global Economic Observer)
With initial low levels of income per capita, a declining population and relatively modest economic growth rates, there are little prospects of diminishing the gap between Romania and the EU countries. Nevertheless, in the long term, convergence is expected. The question then arises, “What are the drivers and their likely potential to boost economic growth and the catching-up process?”. This paper presents shortly the theoretical background of economic convergence and then focuses on the assessment of possible paths of Romania’s convergence towards the EU. Based on the existing long-term macroeconomic projections and the assessment of the possible future developments of the drivers of economic growth, we have built three scenarios of economic convergence, highlighting the possible timespan of convergence. We have employed growth accounting methods to decompose output growth rate into production factors’ contributions (capital and labour) and total factor productivity.